The Adrenal Gland: An Organ Neglected in Pediatric Trauma Cases - Aydogdu, Bahattin; Okur, Mehmet Hanifi; Arslan, Serkan; Arslan, Mehmet Serif; Zeytun, Hikmet; Basuguy, Erol; Icer, Mustafa; Goya, Cemil; Uygun, Ibrahim; Cigdem, Murat Kemal; Onen, Abdurrahman; Otcu, Selcuk (Urology Journal, 2016)
Purpose: Adrenal gland injury (AGI) caused by trauma may cause bleeding and life-threatening problems in children.The objective of this study was to analyze the prevalence of AGI in final diagnoses of trauma. Materials and Methods: The records of 458 patients with abdominal trauma (out of a total 8,200 pediatric patientswith trauma of any sort), who were referred to our clinic between January 2009 and July 2014, were reviewed retrospectively.The numbers of patients with AGI and their ages, gender, trauma patterns, affected organs, pediatrictrauma scores (PTSs), and injury severity scores (ISSs) were recorded, as well as the associated ultrasound (US)and tomographic scan data, treatments, and complications. Computed tomography (CT) scans obtained after traumawere subjected to both primary and secondary evaluation. Results: In total, 28 patients with AGI were detected; their average age was 8.54 ± 4.09 (3-17) years. Twenty(71%) patients were male and 8 (29%) were female. Nineteen (68%) patients had fallen from heights; the mostcommonly injured organs were the kidneys, spleen, and lungs. Injuries were right-sided in 26 (92.9%) patients.The mean ISS was 13.2 (range 5-50) and the mean PTS 8.6 (range 0-11). Seven patients had ISS > 16 and ninehad PTS < 8. AGI was diagnosed by CT in 14 (50%) patients and in 3 (9%) by US at primary evaluation. Uponsecondary scan inspection focusing on the possibility of adrenal gland injury, such injury was ultimately detectedin 28 patients. All patients underwent conservative follow-up, and one died. Conclusion: We recommend calculation of the PTS, as well as other trauma scores, when pediatric patients sufferingmultiple or blunt abdominal trauma(s) present to the emergency . In addition, we believe that in children withtrauma involving the liver, spleen or kidneys, careful evaluation using a CT scan would increase the diagnosis ofAGI and reveal a realistic rate of AGI in trauma cases.